An efficient method of intention understanding and learning for the ambiguous expressions of sentence end. (11th December 2008) - Suzuki, Nobuo; Tsuda, Kazuhiko
In recent years, the usage of Internet and mobile phone has increased explosively and individuals have many more opportunities to send out information over these networks. Considering this media, the styles of writing tend to be more colloquial, where users commonly utilise peculiar expressions such as emoticons, pictograms, three-point leaders and 'taigen-dome' (a Japanese method that ends a sentence with a noun). Although these expressions do not clearly indicate the intentions of the writers, they would be very useful when we understand the intentions and emotions hidden within sentences. And we can use these expressions for recognising emotions efficiently. By focusing on Japanese versions of emoticons and three-point leaders, this paper proposes a method to presume the writers' intentions using the rules extracted from corpora built from data on the Internet. The evaluation tests conducted have produced excellent results for both emoticons and three-point leaders. We also mention reasons of the experimental errors of the rules for emoticons and describe the aspect of the rules for three-point-leaders such as limiting the meaning.